Carbon-coated VOPO4 composite electrode material with expanded interlayer spacing and preparation method and application thereof

By in-situ carbon coating on the VOPO4 electrode material, VOPO4 electrode material with expanded layer spacing is formed, which solves the problems of poor conductivity and small layer spacing of VOPO4 materials, significantly improves the specific capacity and cycle stability of the electrode, and is suitable for magnesium Ionic and zinc ion batteries.

CN119419070APending Publication Date: 2025-02-11CHINA UNIV OF GEOSCIENCES (BEIJING)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411581714.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The existing VOPO4 series materials are difficult to quickly conduct electrons and ions due to poor electrical conductivity and small layer spacing, which hinders their practical application in magnesium and zinc ion batteries.

Method used

By performing in-situ carbon coating on the surface of the VOPO4 electrode material, triethylene glycol is used as the carbon source and layer expansion reagent to form a VOPO4 electrode material with expanded layer spacing, combining organic carbon coating to enhance the conductivity and electronics of the electrode Transmission performance.

Benefits of technology

It has achieved improvements in electrode ion transmission capabilities and improvements in electron transport performance, significantly improved the specific capacity and cycling stability of the material, and is suitable for magnesium ion and zinc ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119419070A_ABST
    Figure CN119419070A_ABST
Patent Text Reader

Abstract

The invention provides a carbon-coated VOPO4 composite electrode material with expanded interlayer spacing and a preparation method and application thereof. The composite material comprises a VOPO4 electrode with enlarged interlayer spacing and an organic carbon coating layer covering the surface of the electrode. Wherein the VOPO4 electrode with the expanded interlayer spacing is of a micro-sphere structure formed by stacking in a nanosheet form, the thickness of the nanosheet is 10-20 nm, and the diameter of the nano-sphere is 3-5 [mu] m; the organic carbon coating layer is formed by calcining triethylene glycol; and the mass ratio of the VOPO4 electrode with the expanded interlayer spacing to the organic carbon coating layer is 10: 1. The composite material is prepared by a hydrothermal synergistic calcination process, and the overall operation is simple, environment-friendly and low in cost. The interlayer spacing of the obtained composite material is remarkably increased, the overall conductivity is effectively improved, and rapid conduction of electrons and ions in the material is facilitated. In addition, the composite material can be used as a positive electrode material of a magnesium ion battery and / or a zinc ion battery, and shows good electrochemical performance and good cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrode materials, and in particular relates to a carbon-coated VOPO4 composite electrode material with enlarged interlayer spacing, and a preparation method and application thereof. Background Art

[0002] Metal ion batteries and capacitors have become a hot topic in the field of energy storage due to their high energy density, safer electrolytes and many other advantages. Among them, divalent ion batteries represented by magnesium and zinc ion batteries have attracted widespread attention and shown great application prospects due to their high theoretical capacity, high energy storage potential and high safety. However, materials that can be used for both magnesium ion batteries and zinc ion batteries are still under development in this field, especially materials that achieve good electrochemical performance and good cycle stability through structural design still face great challenges.

[0003] In the prior art, the positive electrode materials used for magnesium ion batteries mainly include vanadium pentoxide, manganese-based oxides, cobalt-based oxides, etc. The positive electrode materials used for zinc ion batteries mainly include vanadium-based oxides, manganese-based oxides and Prussian blue materials, etc. It can be seen that there is no effective technical solution for positive electrode materials that can be used in multiple different ion battery systems and can maintain good electrochemical properties in different battery systems. However, due to the poor conductivity and small interlayer spacing of traditional VOPO4 series materials, it is difficult to quickly conduct electrons and ions, which seriously hinders its practical application.

[0004] In summary, developing a positive electrode material suitable for magnesium / zinc ion batteries with good electrochemical properties and good cycle stability is an urgent problem to be solved by technicians in this field. Summary of the invention

[0005] In order to overcome the shortcomings of the performance of existing VOPO4 materials and apply them to magnesium ion and / or zinc ion batteries, the present invention provides an expanded layer synergistic carbon-coated positive electrode material, specifically comprising a VOPO4 electrode with an expanded interlayer spacing and an organic carbon coating layer covering the surface of the electrode. The VOPO4 electrode with an expanded interlayer spacing is a structure of micron-spheres formed by stacking nanosheets, the thickness of the nanosheets is 10-20nm, and the diameter of the nanospheres is 3-5μm; the organic carbon coating layer is formed by calcining triethylene glycol; the mass ratio of the VOPO4 electrode with an expanded interlayer spacing to the organic carbon coating layer is 10:1.

[0006] The present invention first prepares a VOPO4 material with an enlarged interlayer spacing as a substrate, and then uses triethylene glycol as a carbon source for in-situ carbon coating on its surface. Among them, the triethylene glycol used can not only be effectively embedded in the material to produce a good expanded layer structure, but also can form amorphous carbon between layers in the subsequent calcination process to play the role of a conductive layer. That is, in the present invention, triethylene glycol is not only used as a carbon source but also as an expansion agent, which is a feature that other carbon sources do not have. The VOPO4 material with an enlarged interlayer spacing improves the electrode ion transmission capacity, while the carbon coating layer improves the electronic transmission performance of the system. The specific ratio of the two is designed, so that the prepared electrode material has obvious advantages such as high specific capacity and good cycle stability.

[0007] Another object of the present invention is to provide a method for preparing the carbon-coated VOPO4 composite electrode material with enlarged interlayer spacing. The overall process is simple and has the advantages of no pollution, low cost, low energy consumption, etc.

[0008] To achieve the above object, the present invention provides a method for preparing a carbon-coated VOPO4 composite electrode material with an enlarged interlayer spacing, which specifically comprises the following steps:

[0009] Step 1: Disperse vanadium pentoxide in water and drop concentrated phosphoric acid solution into the water under stirring;

[0010] Step 2: subjecting the solution obtained in step 1 to reflux reaction at a certain temperature, and after the reaction is completed, filtering to obtain a solid product;

[0011] Step 3: Grind the solid product obtained in step 2, disperse it in isopropanol, and perform ultrasonication to obtain a mixture;

[0012] Step 4: centrifuge the mixture obtained in step 3, mix the separated solid with triethylene glycol, and stir evenly;

[0013] Step 5: Centrifuge the mixture obtained in step 4, and calcine the separated solid under an inert atmosphere to obtain the carbon-coated VOPO4 composite electrode material with an enlarged interlayer spacing.

[0014] In a preferred embodiment, in step 1, the mass volume ratio of the vanadium pentoxide to water is 1 g:(5.2-7.2) ml; preferably, the mass volume ratio of the vanadium pentoxide to water is 1 g:6.25 ml.

[0015] In a preferred embodiment, in step 1, the mass volume ratio of the vanadium pentoxide to the concentrated phosphoric acid solution is 1 g:(4.9-6.8) ml; preferably, the mass volume ratio of the vanadium pentoxide to the concentrated phosphoric acid solution is 1 g:5.8 ml.

[0016] In a preferred embodiment, the concentrated phosphoric acid is saturated concentrated phosphoric acid. Preferably, the concentration of the saturated concentrated phosphoric acid is 85.11%.

[0017] In a preferred embodiment, in step 2, the solution reflux reaction temperature is 150-190° C., and the reaction time is 15-24 h.

[0018] In a preferred embodiment, in step three, the mass volume ratio of the solid to isopropanol is 1 mg:(0.4-0.6) mL; preferably, the mass volume ratio of the solid to isopropanol is 2 mg / mL.

[0019] In the present invention, VOPO4 solid and isopropanol interact under ultrasonic conditions to form a VOPO4 product with an enlarged interlayer spacing. Isopropanol is selected as a pre-expansion agent because isopropanol can form a unique hydrogen bond structure with water, allowing the interlayer water of vanadium pentoxide to be quickly released, thereby facilitating the next step of layer expansion. Preferably, the ultrasonic power is 5-20W and the ultrasonic time is 1-2h.

[0020] In a preferred embodiment, in step 4, the mass volume ratio of the solid to triethylene glycol is 4.8 g: (5-10) mL; preferably, the stirring speed is 100-300 r / min, and the stirring time is 40-60 h.

[0021] In a preferred embodiment, in step five, the inert atmosphere includes argon.

[0022] In a preferred embodiment, in step five, the calcination temperature is 600-700° C., and the calcination time is 1-3 h.

[0023] Another object of the present invention is to provide the above-mentioned carbon-coated VOPO4 composite electrode material with enlarged interlayer spacing as a battery positive electrode, and its use in the preparation of magnesium ion and / or zinc ion batteries.

[0024] The present invention provides a magnesium ion battery, comprising a carbon-coated VOPO4 composite electrode material with enlarged interlayer spacing as a positive electrode, a magnesium metal electrode as a negative electrode, and an electrolyte of a Mg(TFSI)2 solution dissolved in dimethyl ether.

[0025] In a preferred embodiment, the specific capacity of the magnesium ion battery can reach 217.6 mAh g -1 After 800 charge and discharge cycles, the remaining capacity is 191.3 mAh g -1 .

[0026] The invention provides a zinc ion battery, comprising a carbon-coated VOPO4 composite electrode material with enlarged interlayer spacing as a positive electrode, a zinc metal electrode as a negative electrode, and a zinc sulfate solution as an electrolyte.

[0027] In a preferred embodiment, the specific capacity of the zinc ion battery can reach 356.2 mAh g -1 After 500 charge and discharge cycles, the remaining capacity is 304.2 mAh g -1 .

[0028] Compared with the prior art, the technical solution of the present invention has the following advantages:

[0029] The overall preparation method of the present invention is easy to operate and is green and environmentally friendly. Whether it is preparing VOPO4 materials with enlarged interlayer spacing or in-situ carbon coating with triethylene glycol as the carbon source, it has the significant advantages of low cost and low energy consumption. When the prepared material is used as the positive electrode material of magnesium ion and / or zinc ion batteries, its specific capacity, energy density and cycle stability are significantly improved. Specifically, the magnesium ion battery assembled with the obtained composite material as the positive electrode, magnesium metal as the negative electrode, and Mg(TFSI)2 solution dissolved in dimethyl ether as the electrolyte exhibits a high specific capacity of 217.6 mAh g -1 The specific capacity and good cycle stability (after 800 charge and discharge cycles, the specific capacity remained 191.3 mAh g -1 The composite material was used as the positive electrode, zinc metal as the negative electrode, and 2M zinc sulfate solution as the electrolyte. The assembled zinc ion battery showed a high capacity of 356.2 mAh g -1 The specific capacity and good cycle stability, after 500 charge and discharge cycles, the specific capacity remained 304.2 mAh g -1 . BRIEF DESCRIPTION OF THE DRAWINGS

[0030] These and / or other aspects and advantages of the present invention will become more clear and easier to understand from the following detailed description of the embodiments of the present invention in conjunction with the accompanying drawings, in which:

[0031] Figure 1 This is a SEM image of a composite material of an expanded layer and synergistic carbon-coated positive electrode material prepared in Example 1 of the present invention, with a magnification of 5000;

[0032] Figure 2 This is a SEM image of a composite material of an expanded layer and carbon-coated positive electrode material prepared in Example 1 of the present invention, with a magnification of 40,000;

[0033] Figure 3 The specific capacitance test of the magnesium ion battery prepared in Example 1 of the present invention at different current densities;

[0034] Figure 4 The cycle performance test of the magnesium ion battery prepared in Example 1 of the present invention;

[0035] Figure 5 The specific capacitance test of the zinc ion battery prepared in Example 2 of the present invention at different current densities;

[0036] Figure 6 Cyclic performance test of the zinc ion battery prepared in Example 2 of the present invention;

[0037] Figure 7 This is a cycle performance test of the magnesium ion battery prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0038] In order to enable those skilled in the art to better understand the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and specific implementation methods, but it should be understood that the protection scope of the present invention is not limited to the specific implementation methods.

[0039] Unless otherwise specified, the technical means used in the present invention are conventional means well known to those skilled in the art, and the various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods. The reagents used in the present invention are analytically pure unless otherwise specified. In the present invention, parts by weight can be weight units known in the art such as μg, mg, g, kg, etc., or multiples thereof, such as 1 / 10, 1 / 100, 10 times, 100 times, etc.

[0040] Example 1

[0041] Step 1: Weigh 4.8 g of vanadium pentoxide and disperse it in 30 mL of water. Add 28 mL of saturated concentrated phosphoric acid solution dropwise while stirring.

[0042] Step 2: The solution obtained in step 1 is heated to reflux at 160° C. for 20 h, and then filtered to obtain a solid product;

[0043] Step 3: Grind the solid product obtained in step 2, then disperse it in isopropanol at a concentration of 2 mg / mL, and perform ultrasonic treatment at a power of 10 W for 2 hours;

[0044] Step 4: The mixture of the products in step 3 was centrifuged, and the separated solid was mixed with triethylene glycol at a mass volume ratio of 4.8 g:5 mL, and stirred at a rate of 200 r / min for 48 h.

[0045] Step 5: Centrifuge the mixture obtained in step 4, and calcine the obtained solid under argon atmosphere at a temperature of 650° C. for 2 h to obtain a carbon-coated VOPO4 composite electrode material with an enlarged interlayer spacing.

[0046] Its microscopic appearance is Figure 1 and Figure 2 As shown in the figure, it can be seen that the composite material prepared in this embodiment is in the morphology of micron-spheres formed by stacking VOPO4 nanosheets, and the surface of a single nanosheet is rough, indicating that its surface is coated with carbon particles.

[0047] The composite materials were prepared into pole pieces and assembled into magnesium ion batteries, and their performance was tested.

[0048] The magnesium ion battery assembly method comprises the following steps:

[0049] (1) The prepared sample was mixed with super P and PVDF in a mass ratio of 8 / 1 / 1, coated on a Ti foil current collector after mixing evenly, and dried at 120° C. for 20 h to obtain a magnesium ion battery positive electrode.

[0050] (2) The above positive electrode and magnesium foil negative electrode were placed in a 0.5 M Mg(TFSI)2 dimethyl ether electrolyte to form a button cell.

[0051] The performance of magnesium ion batteries was tested, and the results are as follows Figure 3 and Figure 4 As shown. Figure 3 It can be seen that the obtained sample is at 0.1Ag -1 The current density can reach about 217.6 mAh g -1 The specific capacity of 1Ag -1 The current density can still maintain about 122.8 mAh g -1 The specific capacity shows good rate performance. Figure 4 The results show that the obtained battery has good cycle stability.

[0052] Example 2

[0053] The composite material obtained in Example 1 was prepared into pole pieces and assembled into zinc ion batteries, and their performance was tested.

[0054] The zinc ion battery assembly method comprises the following steps:

[0055] (1) The prepared sample was mixed with super P and PVDF in a mass ratio of 8 / 1 / 1, a small amount of N-methylpyrrolidone was added, the mixture was evenly coated on Ti foil, and the mixture was dried at 100°C in vacuum for 12 h to obtain a positive electrode for a zinc ion battery.

[0056] (2) The above positive electrode and zinc foil negative electrode were mixed in 2 mol L -1 The button cell is composed of ZnSO4 electrolyte.

[0057] The performance of zinc ion batteries was tested and the results were as follows Figure 5 and Figure 6 As shown. Figure 5 It can be seen that the obtained sample is at 0.5Ag -1 The current density can reach 356.2mAh g -1 The specific capacity at 1.0A g -1 The current density can reach 313.4 mAh g -1 The specific capacity of Figure 6 The results show that after 500 charge and discharge cycles, the sample has a residual capacity of 304.2 mAhg -1 .

[0058] Example 3

[0059] Except that the amount of triethylene glycol in step 4 was changed to 10 mL, the other steps were exactly the same as those in Example 1. The electrochemical test was a magnesium ion battery test, in which the magnesium ion battery was tested at 0.1 Ag. -1 The current density can reach 209.1mAh g -1 The capacity of the battery is similar to that of the magnesium ion battery in Example 1.

[0060] Example 4

[0061] Except that the amount of triethylene glycol in step 4 was changed to 10 mL, the other steps were exactly the same as those in Example 2. The electrochemical test was a zinc ion battery test. The zinc ion battery was tested at 0.5 Ag. -1 The current density can reach 349.5 mAh g -1 The specific capacity of the battery is similar to that of the battery in Example 2.

[0062] Example 5

[0063] Except that the calcination temperature in step 5 was changed to 700°C, the other steps were exactly the same as those in Example 1. The electrochemical test was a magnesium ion battery test. -1 The current density can reach 124.5 mAh g -1 The capacity of the battery is similar to that of the magnesium ion battery in Example 1.

[0064] Example 6

[0065] Except that the calcination temperature in step 5 was changed to 700°C, the other steps were exactly the same as those in Example 2. The electrochemical test was a zinc ion battery test. The zinc ion battery was tested at 1.0Ag. -1 The current density can reach 319.2 mAh g -1 The capacity of the battery is similar to that of the zinc ion battery in Example 2.

[0066] Comparative Example 1

[0067] Step 5 is modified as follows: centrifuge the mixture obtained in step 4, and dry it at 60° C. to obtain an electrode material. Other method steps are exactly the same as those in Example 1. The electrochemical test is a magnesium ion battery test.

[0068] The results are as follows Figure 7 As shown. It can be seen from the cycle test data that since the material obtained in this comparative example has not been calcined, no carbon coating layer is produced, and its power transmission performance is reduced, making the cycle stability of the battery significantly weaker than that of the electrode in Example 1. This illustrates the importance of using the carbon coating layer for modification.

[0069] The foregoing description of specific exemplary embodiments of the present invention is for the purpose of illustration and demonstration. These descriptions are not intended to limit the present invention to the precise form disclosed, and it is clear that many changes and variations can be made based on the above teachings. The purpose of selecting and describing the exemplary embodiments is to explain the specific principles of the present invention and its practical application, so that those skilled in the art can realize and utilize various different exemplary embodiments of the present invention and various different selections and changes. The scope of the present invention is intended to be limited by the claims and their equivalents.

Claims

1. A carbon-coated VOPO4 composite electrode material with enlarged interlayer spacing, characterized in that: The material includes a VOPO4 electrode with an enlarged interlayer spacing and an organic carbon coating layer covering the surface of the electrode; wherein the VOPO4 electrode with an enlarged interlayer spacing is a structure of micron-sized balls piled up in the form of nanosheets, the thickness of the nanosheets is 10-20nm, and the diameter of the nanospheres is 3-5μm; the organic carbon coating layer is formed by calcining triethylene glycol; the mass ratio of the VOPO4 electrode with an enlarged interlayer spacing to the organic carbon coating layer is 10:

1.

2. The method for preparing the carbon-coated VOPO4 composite electrode material with enlarged interlayer spacing as claimed in claim 1, characterized in that: The following steps are involved: Step 1: Disperse vanadium pentoxide in water and drop concentrated phosphoric acid solution into the water under stirring; Step 2: subjecting the solution obtained in step 1 to reflux reaction at a certain temperature, and after the reaction is completed, filtering to obtain a solid product; Step 3: Grind the solid product obtained in step 2, disperse it in isopropanol, and perform ultrasonication to obtain a mixture; Step 4: centrifuge the mixture obtained in step 3, mix the separated solid with triethylene glycol, and stir evenly; Step 5: Centrifuge the mixture obtained in step 4, and calcine the separated solid under an inert atmosphere to obtain the carbon-coated VOPO4 composite electrode material with an enlarged interlayer spacing.

3. The method for preparing the carbon-coated VOPO4 composite electrode material with enlarged interlayer spacing as claimed in claim 2, characterized in that: In step 1, the mass volume ratio of the vanadium pentoxide to the concentrated phosphoric acid solution is 1 g: (4.9-6.8) ml.

4. The method for preparing the carbon-coated VOPO4 composite electrode material with enlarged interlayer spacing as claimed in claim 2, characterized in that: In step 2, the solution reflux reaction temperature is 150-190° C., and the reaction time is 15-24 h.

5. The method for preparing the carbon-coated VOPO4 composite electrode material with enlarged interlayer spacing as claimed in claim 2, characterized in that: In step 3, the mass volume ratio of the solid to isopropanol is 1 mg: (0.4-0.6) mL.

6. The method for preparing the carbon-coated VOPO4 composite electrode material with enlarged interlayer spacing as claimed in claim 2, characterized in that: In step 4, the mass volume ratio of the solid to triethylene glycol is 4.8 g: (5-10) mL.

7. A magnesium ion battery, characterized in that: The invention comprises the composite material as claimed in claim 1 as a positive electrode, a magnesium metal electrode as a negative electrode, and an electrolyte which is a solution of Mg(TFSI)2 dissolved in dimethyl ether.

8. The magnesium ion battery according to claim 7, characterized in that The specific capacity of the magnesium ion battery can reach 217.6 mAh g -1 After 800 charge and discharge cycles, the remaining capacity is 191.3 mAh g -1 .

9. A zinc ion battery, characterized in that: The invention comprises the composite material as claimed in claim 1 as a positive electrode, a zinc metal electrode as a negative electrode, and a zinc sulfate solution as an electrolyte.

10. The zinc ion battery according to claim 9, characterized in that: The specific capacity of the zinc ion battery can reach 356.2 mAh g -1 After 500 charge and discharge cycles, the remaining capacity is 304.2 mAh g -1 .